Design of a battery-operated portable DC power supply. Part 1 : voltage output control - Neo, Wei Xiang (2018)
Batteries are the common source of power supply in human’s daily lives. This form of power supply is applicable to a wide range of electronics devices. However, using just batteries is impractical to supply applications (i.e. motors) that requires high input voltage supply. Hence, a DC-to-DC boost converter is implemented to supply such high voltage rating application with minimal input voltage supply. DC-to-DC boost converter can convert the input voltage supply from batteries to an adjustable output voltage that is much higher in magnitude. Adjustable output voltage level opens to a wide range of load that can be connected to the output terminals of the boost converter. Furthermore, the implementation of smart technology into this system would enhance its usability. The full integration of the output voltage control can be controlled remotely via the smart technology of Bluetooth connection. Using digital technology, the output voltage that is generated from the boost converter is of higher precision as compared to manual tuning of potentiometer. This would prevent damages from overvoltage and not endangered the life of the others.